2015
DOI: 10.1097/ta.0000000000000675
|View full text |Cite
|
Sign up to set email alerts
|

Impact of preseason concussion education on knowledge, attitudes, and behaviors of high school athletes

Abstract: Background The benefit of preseason concussion education on athletes’ knowledge, attitudes, and behaviors is unclear. The purpose of the study was to determine the influence of preseason concussion education on knowledge and self-reported attitudes and reporting behaviors. We hypothesized that preseason education would lead to better knowledge and self-reported attitudes and better reporting of concussion symptoms during the season. Methods Prospective cohort comparing the benefits of a preseason lectured-ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
94
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(98 citation statements)
references
References 50 publications
4
94
0
Order By: Relevance
“…All studies included in this review developed a unique questionnaire based upon the literature, consensus statements, position statements, educational resources (e.g., CDC's Heads Up materials), Sport Concussion Assessment Tool (SCAT), and/or expert opinions. Five studies adopted and/or slightly modified a previously utilized survey (Anderson, Gittelman, Mann, Cyriac, & Pomerantz, 2016;Gourley, Valovich McLeod, & Bay, 2010;Kurowski, Pomerantz, Schaiper, & Gittelman, 2014;Kurowski, Pomerantz, Schaiper, Ho, & Gittelman 2015;Shroyer & Stewart, 2016).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…All studies included in this review developed a unique questionnaire based upon the literature, consensus statements, position statements, educational resources (e.g., CDC's Heads Up materials), Sport Concussion Assessment Tool (SCAT), and/or expert opinions. Five studies adopted and/or slightly modified a previously utilized survey (Anderson, Gittelman, Mann, Cyriac, & Pomerantz, 2016;Gourley, Valovich McLeod, & Bay, 2010;Kurowski, Pomerantz, Schaiper, & Gittelman, 2014;Kurowski, Pomerantz, Schaiper, Ho, & Gittelman 2015;Shroyer & Stewart, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…For instance, Bloodgood et al (2013) revealed that only a quarter of both athletes and parents knew a concussion can be caused by a blow other than to the head. Similarly, other studies suggested knowledge deficits (i.e., only 58-61% of respondents answered correctly) in understanding the causes of concussions among parents (Mannings et al, 2014) and athletes (Kurowski et al, 2014;Kurowski et al, 2015).…”
Section: Youth Concussion Factsmentioning
confidence: 99%
See 2 more Smart Citations
“…11 Of interest to us are the multiple studies that provide insight regarding secondary school athletes and concussion education. 2,8,[13][14][15][16][17][18] One such study determined that secondary school athletes with previous formal concussion education are more likely to notify their coaches of concussion symptoms. 15 Secondary school athletes with a previous history of concussion are also more likely to report concussion symptoms.…”
Section: Introductionmentioning
confidence: 99%